Complicated jejunal diverticulitis: A case report and review of literature. Issue 11 (15th November 2022) - Scheese, Daniel; Alwatari, Yahya; Khan, Jamal; Slaughter, Ashley
Abstract: Jejunal diverticulitis is an uncommon pathology wherein a delay in diagnosis can lead to significant morbidity and mortality. We report a case of such diverticula requiring operative management, after patient failed non‐operative management, likely due to advanced jejunal inflammation from a delay in diagnosis and subsequent management. Abstract : With a low reported incidence rate, jejunal diverticulitis can be easily overlooked in elderly patients presenting with nausea and abdominal pain. A delay in diagnosis and treatment has potential for intestinal obstruction, bleeding, and perforation. Mortality rates of 40% have been reported in cases of perforation secondary to jejunal diverticulitis.